Let's be friends with ourselves! / Dr Nur Ilianis Adnan - Adnan, Nur Ilianis (Academy of Language Studies, 2023)
From the book, 'Master your mind' by Roger Seip and Robb Zbierski, having a two-hour weekly meeting with yourself can help you to reconnect with the things that mean the most to you. You can review the big-picture of your vision, dreams, and goals. Remember, this meeting is NOT a time for you to create your to-do list. It is a time that allows you to gain clarity on what you want to accomplish, set intentions for the week and practice visualising - getting what you want out of your days. With a lot of things going on in our lives, we can sometimes go off-track very easily. Hence, it is best for us to have 'meeting' with ourselves with no distractions, gadgets and social media. Just you and yourself. You can bring along a pen and a notebook for you to write down the necessary things. If it is rather difficult to get a 2-hour in a week for you to do this, try making it once every 2 weeks or once a month. Try to get the 2- hour for YOURSELF.